PENGEMBANGAN BUDIDAYA PORANG DI LAHAN BAWAH TEGAKAN POHON DI DESA PACAREJO, KECAMATAN SEMANU, KABUPATEN GUNUNGKIDUL - Sumarwoto Ps; Oktavia S. Padmini; Dwi Aulia Puspitaningrum (Dharma: Jurnal Pengabdian Masyarakat, 2020)
Pacarejo Village in Semanu District Gunung Kidul Regency is a village where is still a lots of potential lands under Tree forest stands.  Land Proverties taht belonging of  Universitas Pembangunan Nasional Veteran Yogyakarta  (UPNVYK) located in this place. It is available to cultivate Porang stalk. Porang is going to growing well, if there are shading plants, in the form of stands.There are still capable of about 50 percent light. The land in Pacarejo Village is overgrown with teak, sonokeling, mahony and sengon trees. It is rich and get benefits apart from the timber, soo the land underneath can be used for plant that can provide yields well. In other hand, this activities provide economic added value to the community around the forest and get the better welfare. This Community servises activity aims to cultivate land, including UPNVYK land which has not been utilized as well as to be used as a forum for education for the community and can obtain additional results, thereby improving the local community's economy. The program dedicated to improve the commnunity empowerment. In program implementation, we conduct with communities approach methode. It was carried out using the RRA (Rapid Rural Approach) and PRA (Participatory Rural Approach) methods, which are the  philosophy  model to close the village community deeply. All of Activities have been doing by Focus Group Discussion (FGD), get the extention to the community, dissemination commodities of Porang and its benefits of commodities.  The program are cultivate land with Porang and make the derivative product after harvest handling. To get the ideal of the program, to be done through scheduled mentoring,  implementation of technology, controlling and monitoring. The application of the method, in the form of activities by presenting a "demplot" of Porang cultivation and assistance properly and correctly. It is able to carry out the cultivated of post-harvest handling and calculated  revenue to be get economical benefit. The results of the activities showed that the program is useful and able to get the   land use optimal and the end of the program will increase household community income.